A política centralizadora de D. Dinis e a resistência nobiliárquica de D. Afonso e seus herdeiros (1271-1315) - Zlatic, Carlos Eduardo (2012)
From documentary sources integrated by genealogies, chronicles and royal documents, this paper intend to broach the reign of King D. Dinis (1261-1325, king from 1279) and attitudes of D. Afonso, Lusitanian king's brother, and his daughters against this government. The sixth king of Portugal used their status of sovereign and supreme keeper of justice to undertake the process of control and attack to the rights of nobility intending to centralize the power of the Portuguese Crown. In the position of noble, D. Afonso was directly aggrieved by the royal policy and reacted to the attacks of their privileges with three riots started in 1281, 1287 and 1299. That also was part of strengthening political maneuvers of this infant: his marriage, and that of his daughters, with members of the Castilian nobility, aiming to expand alliances and thus his power against D. Dinis. Although D. Alfonso did not have obtained victories in their battles, or even may have blunted the momentum of the centralizing monarch Lusitanian, the infant started the revolt of this reign, whose end was marked by civil war of 1319-1324.